Pharmacokinetic interactions between quinine and lopinavir/ritonavir in healthy Thai adults - Siwalee Rattanapunya (2018)
© 2015 by The American Society of Tropical Medicine and Hygiene. This study aimed to investigate the pharmacokinetic interactions between quinine and lopinavir boosted with ritonavir (LPV/r) in healthy Thai adults (8 males and 12 females). Period 1 (day 1): subjects received a single oral dose of 600 mg quinine sulfate. Period 2: subjects received LPV/r (400/100 mg) twice daily. Period 3: subjects received a single quinine sulfate dose plus LPV/r twice a day. Intensive blood sampling was performed during each phase. Quinine AUC 0-48h (area under the plasma concentration-time curve from time 0 to 48 hours), AUC 0-∞ (area under the plasma concentration-time curve from time 0 to infinity), and C max (maximum concentration over the time-span specified), were 56%, 57%, and 47% lower, respectively, in the presence of LPV/r. 3-Hydroxyquinine AUC 0-48h , AUC 0-∞ , and C max were significantly lower and the metabolite-to-parent ratio was significantly reduced. Lopinavir and ritonavir exposures were not significantly reduced with quinine coadministration, but C max of both drugs were significantly lower. The geometric mean ratio (GMR) and 90% CI of AUC 0-48h , AUC 0-∞ and C max for quinine, 3-hydroxyquinine, lopinavir, and ritonavir lay outside the bioequivalent range of 0.8-1.25. Drug treatments during all periods were generally well tolerated. The reduction in systemic exposure of quinine and 3-hydroxyquinine with concomitant LPV/r use raises concerns of suboptimal exposure. Studies in HIV/malaria coinfection patients are needed to determine the clinical impact to decide if any change to the quinine dose is warranted.